Identifikasi Dampak Perkembangan Pariwisata terhadap Lingkungan di Desa Canggu, Kecamatan Kuta Utara, Kabupaten Badung - Wahyundaria, Dwi Ajeng; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2021)
The development of Canggu Village tourism began in the 1980s with tourists looking for waves at Canggu beach for surfing. This research aims to find out the impact of tourism development on environmental conditions in the village of Canggu North Kuta Badung Regency. In this case, it covers the environmental conditions of tourism in general, such as; attractions, facilities, infrastructure, transportation includes land and water. The research used qualitative method with observation and unstructured interviews. The primary data in this study is data sourced from direct to the research location by means of observation and. While the secondary data in this study is data obtained from other sources to complete the primary data obtained in the field. The informant determination technique used is a purposive technique, aimed at members of the public who know and are affected by the development of tourism in this village. The results showed that supporting infrastructure such as road access, sidewalks, parking lots as well as street lighting infrastructure (LPJ) in Canggu Village are still minimal, especially for roads, currently still quite narrow so that traffic jams often occur. The area of agricultural land in Canggu Village has decreased dramatically in the past five years, from 2010 to 2015 around 28 ha, due to the transfer of agricultural land functions into tourism accommodation and residential areas. Through the decline of agricultural land, affecting water conditions in Canggu Village, the number of villa businesses, restaurants, cafes, and laundry, most do not have good management of liquid waste reservoirs that pollute irrigation channels and rivers in Canggu Village. This not only resulted in damage to irrigation channels but also water pollution used by irrigation in agricultural land or rice fields. This situation has shifted the culture of farming and Subak activities in Canggu Village caused by the development of tourism in this village. Keyword: Identification, Impact of Tourism Development, Environment, Canggu